The control of sclerotinia stem rot on oilseed rape (Brassica napus): current practices and future opportunities - Derbyshire, Mark; Denton-Giles, Matthew (Wiley-Blackwell, 2016)
Sclerotinia stem rot (SSR) caused by the phytopathogenic fungus Sclerotinia sclerotiorum is a major disease of oilseed rape (Brassica napus). During infection, large, white/grey lesions form on the stems of the host plant, perturbing seed development and decreasing yield. Due to its ability to produce long-term storage structures called sclerotia, S. sclerotiorum inoculum can persist for long periods in the soil. Current SSR control relies heavily on cultural practices and fungicide treatments. Cultural control practices aim to reduce the number of sclerotia in the soil or create conditions that are unfavourable for disease development. These methods of control are under increased pressure in some regions, as rotations tighten and inoculum levels increase. Despite their ability to efficiently kill S. sclerotiorum, preventative fungicides remain an expensive gamble for SSR control, as their effectiveness is highly dependent on the ability to predict the establishment of microscopic infections in the crop. Failure to correctly time fungicide applications can result in a substantial cost to the grower. This review describes the scientific literature pertaining to current SSR control practices. Furthermore, it details recent advances in alternative SSR control methods including the generation of resistant varieties through genetic modification and traditional breeding, and biocontrol. The review concludes with a future directive for SSR control on oilseed rape.